VIABILITAS Lactobacillus rhamnosus SKG 34 DALAM BERBAGAI JENIS ENKAPSULAN DAN SUHU PENYAJIAN - Permatasari, Adiel Kunti; Nocianitri, Komang Ayu; Djuniaji, Agus Slamet (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 5 No 1 (2016): Jurnal ITEPA, 2016)
This research was conducted to determine the viability of Lactobacillus rhamnosus SKG 34 on various encapsulant and temperature. This research was divided into two steps. The first step, three kinds of encapsulant agent, i.e. maltodextrin, carrageenan, and alginate were used to microencapsulate Lactobacillus rhamnosus SKG 34. At this step, microcapsule yield, morphology, and viability of Lactobacillus rhamnosus SKG 34 was observed. Encapsulant with the highest population of Lactobacillus rhamnosus SKG 34 was extended into the second step. At the second step, microcapsule was treated with 7 variants of temperature, i.e. 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, and 75°C. Data obtained were shown and explained with descriptive method. The result of the research showed that encapsulant variety gave different effects on microcapsule yield, morphology and viability of Lactobacillus rhamnosus SKG 34. The highest population produced by maltodextrin (1,24 x 109 ± 0,33 cfu/gr). The highest viability obtained at 45°C (3,37 x 108 ± 0,14). Lactobacillus rhamnosus SKG 34 can survive at adequate amount to give functional effect to the body with maximum temperature 55°C (4,78 x 107 ± 0,31cfu/ml).
Keywords: Microencapsulation, Lactobacillus rhamnosus SKG 34, maltodextrin, carrageenan, alginate, temperature